If it's not what You are looking for type in the equation solver your own equation and let us solve it.
k in (-oo:+oo)
2*(6*k+3) = 54 // - 54
2*(6*k+3)-54 = 0
2*(6*k+3)-54 = 0
12*k-48 = 0
12*k-48 = 0
12*k-48 = 0 // + 48
12*k = 48 // : 12
k = 48/12
k = 4
k = 4
| 4(-5x-6)=-224 | | 6(9+3d)=-36 | | 5(-1+3b)=160 | | 2(-6w-8)=-40 | | x-(24/x)=2 | | 7(2x+6)=168 | | 5(3-w)=70 | | 7(4t+8)=280 | | -3/4x-8=13 | | 23=.15x+5 | | 40=x+8 | | 4.2x-6.2=1-1.1x | | 6x(x-4)-16x^2-(9x-1)= | | 6(2+7w)=-240 | | x+11=23-5x | | 2(5a-1)=-102 | | 6(5w+6)=186 | | 3(-4+7t)=-180 | | 7(3+d)=28 | | 4(-7n+5)=-92 | | -50h+750=-185+35h | | 4(-3x-6)=-24 | | 2(7w+6)=40 | | 2(1w+7)=24 | | 7(10+4a)=154 | | 2(4m-7)=-110 | | 5(-2-3n)=80 | | 5(7+3w)=-145 | | 3(9-5b)=-18 | | 4(5a+10)=-20 | | 3(-2+4x)=-6 | | 6(-2d+7)=54 |